2018
DOI: 10.2169/internalmedicine.0967-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Clinical Performance of the New 19-G ViziShot FLEX and 21- or 22-G ViziShot 2 Endobronchial Ultrasound-guided Transbronchial Needle Aspiration Needles

Abstract: Objective Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a minimally invasive procedure for pulmonary and mediastinal diseases. This study compared the performance of a novel 19-G needle with a 21- or 22-G needle. Patients and Methods Eleven patients at Okayama Medical Center were enrolled retrospectively between April and December 2017. Enlarged lymph nodes and a pulmonary nodule were sampled with both 19-G and 21- or 22-G needles in nine patients. Two patients underwent biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Both concluded that although sensitivity for each needle alone was similarly high, the additional pass with the 19-G resulted in a statistically significant increase in the overall diagnostic yield, from 92% to 99% (p = 0.045), suggesting an improved performance of the 19-G needle compared with the 21-G or 22-G needles. 12,16,17 However, we found no significant difference in diagnostic yield between the 19-G, 21-G and 22-G needles in this metaanalysis.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Both concluded that although sensitivity for each needle alone was similarly high, the additional pass with the 19-G resulted in a statistically significant increase in the overall diagnostic yield, from 92% to 99% (p = 0.045), suggesting an improved performance of the 19-G needle compared with the 21-G or 22-G needles. 12,16,17 However, we found no significant difference in diagnostic yield between the 19-G, 21-G and 22-G needles in this metaanalysis.…”
Section: Discussioncontrasting
confidence: 69%
“…12,19,21,22 However, we observed no difference in sensitivity resulting from the application of ROSE, and in fact, studies that did not use ROSE presented a higher diagnostic sensitivity. Minami et al 17 reported the lowest sensitivity out of all studies while implementing this histopathologic evaluation, possibly due to the low number of participants. One study from Japan analysed their samples with and without ROSE but did not provide detailed information for each subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…7 Whether the newer, larger 19-gauge needles confer an advantage over smaller needles is the subject of ongoing investigation. [15][16][17] The use of EBUS for extracting lymph node biopsy specimens with forceps rather than with needle aspiration has been described, and results suggest that the combination of both techniques improves yield over SOC alone. [18][19][20] In a significant number of patients, however, the forceps encounter resistance and consequently does not pass reliably through the bronchial wall and into the targeted lymph node.…”
mentioning
confidence: 99%
“…PD-L1 positivity appears to be higher in certain patients with NSCLC: males, smokers, advanced pathologic stages, positive vessel invasion, and positive lymphatic invasion (27). Tissue specimens derived from EBUS-TBNA has been found to be reliable to perform molecular bio-marker analysis (28). However, this is dependent on the cutoff value used for a sample to be considered PD-L1 positive (29).…”
Section: Diagnosis and Staging Of Nsclcmentioning
confidence: 99%